A COMPARISON OF THE HEART, TIMI AND GRACE SCORES IN THE PREDICTION OF A MAJOR ADVERSE CARDIAC EVENT (MACE) IN PATIENTS PRESENTING WITH UNDIFFERENTIATED CARDIAC CHEST PAIN: A PROSPECTIVE COHORT STUDY IN A UK POPULATION. Issue 12 (18th November 2016) - Reaney, PD; Elliott, H; Cooper, J
Abstract : Objectives & Background: Cardiac sounding chest pain is one of the commonest reasons for presentation to the Emergency Department (ED) or acute medical receiving. An electrocardiogram (ECG) can rapidly identify those patients suffering from an ST elevation acute coronary syndrome (ACS) but the differentiation of patients with non ST elevation ACS from those with non cardiac chest pain or stable cardiac disease is often not straightforward and encompasses historical, clinical and biochemical factors. Effective early risk stratification of this group of non ST elevated ACS patients may streamline care pathways for those at high risk and lead to effective use of resources and early discharge in those in whom ACS is unlikely. Methods: A prospective cohort study of adult patients presenting to the ED or acute medical receiving unit of Aberdeen Royal Infirmary with cardiac sounding chest pain and an a non-diagnostic ECG. A necessary sample size of 1000 patients was calculated and recruitment began in December 2014. HEART, GRACE and TIMI scores were calculated from data obtained on patient attendance, with subjective aspects entered by the attending medical practitioner in real time. Patients were followed up to 30 days for the development of a MACE. Receiver Operated Characteristic (ROC) curves were plotted to determine discriminative power of each of the three scores to detect MACE. Sensitivities and specificities (with 95% CIs) for each score (at different cut-offs) were calculated. Results: Preliminary results are available on 605 patients. Ages ranged from 20–95 years (mean 61.8 years), 360 (59.5%) were male and 108 patients (17.9%) patients suffered a MACE at 30 days. Area under the ROC curves demonstrated that HEART (0.86) had a greater ability to discriminate patients going on to develop a MACE than TIMI (0.71) and GRACE (0.76) scores. Within the HEART low risk group 1.2% of patients developed a MACE and within the high risk group over 60% developed a MACE. Conclusion: The HEART score out performs GRACE and TIMI in predicting MACE in patients presenting to the ED with cardiac sounding chest pain. It rapidly identifies a low-risk population that may be suitable for early discharge or ambulatory management from the ED and higher risk patients may be promptly prioritised for invasive management.Figure 1 Table 1